The Mystère d'Adam and Christian Memory - Mazzaro, Jerome (Comparative drama, 1997)
1 COMPABATIVB i ama Volume 31Winter 1997-98Number 4 The Mystère d'Adam and Christian Memory Jerome Mazzaro As it survives, the Mystère d'Adam is almost certainly incomplete and uncertain as to when in the year it was performed .1 What exists are three episodes, written in octosyllabic and decasyllabic verse and indebted to two different sources. The first of these episodes recounts the Fall (1-590); the second, Cain's murder of Abel (591-744); and the last offers a procession of prophets predicting Christ's birth (745-944). Interweaving these episodes are Latin stage directions, readings, and responsories . In Christian Rite and Christian Drama in the Middle Ages (1965), O. B. Hardison, Jr., argues the author's direct debt to the Liber responsalis or Book of Responses for Sexagésima for eight responsories that the choir sings at key points in the play. These responsories from Genesis provide the outline for the play's first two episodes in accounts of man's creation and the murder of Abel. In the Middle Ages, these readings would have occurred on the second Sunday before Lent, or seven weeks before Easter.2 Earlier, in Les prophètes du Christ (1878), Marius Sepet had connected the last episode of the drama to the pseudo-Augustinian sermon Contra Judaeos, Paganos et Arianes. In that fifth-century sermon, numerous Old Testament figures appear and denounce faithlessness. They remind audiences that even Jewish and Pagan 481 482Comparative Drama prophets foresaw Christ's divinity. The sermon was widely known, and it was often read on the fourth Sunday of Advent, on the day before Christmas, on Christmas, and on the Feast of the Circumcision (1 January). While indicating an inventiveness on the playwright's part in linking these unrelated texts, their combination suggests at least two separate playing dates and resolutions . One source ties the play's performance to Easter and projects an ending in Hell's harrowing; the other connects it to Christmas and posits a concluding Nativity. A third "neutral" performance date is offered in Grace Frank's The French Medieval Drama. Citing the play's costumes and the statement that it be performed outdoors, Frank hazards a playing date in midsummer common for cyclical drama.3 Composed in Anglo-Norman sometime between 1146 and 1175, the Mystère d'Adam chooses not—as had the anonymous twelfth-century Montecassino Passion—to focus narrowly on events in the life of Christ. Nor does it intend, as had The Song ofRoland (c.llOO), to bring hearers immediately into participation in a holy war. Claiming to be neither divinely instituted nor addressed to God—as is liturgy or even the prose of St. Augustine 's Confessions—the play does not unite believers for all time or keep by special revelation to specific events, language, stylization , and spectacle. Its action occurs outside the church, and in its appeal to other humans it is free to be inventive in its selecting and developing incidents and methods of presentation—granted that it contains Figura as God, and in so doing, it presents deity directly. In this area, it relies heavily on vestments, biblical language, and Church teachings. But the overall mimetic thrust of the play is mnemonic and devotional. It seeks to bring human understanding and character into harmony with deity as revealed through universal history. Its intent is, as Augustine says in Epístola 155, momentary unions of its audience in recognitions of their worldly relations to God as defined by his mercy and their origin, nature, and condition. Complementing this intent is guidance , as audiences see presented before them timeless and timely moral questions whose interiorized and contemplated solutions draw memories closer to God. As such, the presentation recognizes audience desires, habits, reasoning methods, emotions, and the kinds of things to which audiences are most likely to assent. Bringing its audiences to God's love through models of service and likeness, the play uses popular memory models in which, as in the Confessions, perceptions of divine will and mercy precede conversion. Jerome Mazzaro483 The play's stage directions reveal sophisticated staging methods that are consonant with Ernst Curtius's account of a revival of...